2019
DOI: 10.3390/ijerph16020253
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Quality of Life at 6 Weeks Postpartum: Influence of the Discomfort Present in the Puerperium

Abstract: Background: Discomfort during the puerperium period is very frequent in the lives of women but the influence of this discomfort on the women’s quality of life has been little studied. The objective of this study is to establish the association between discomfort and frequent problems of women in the puerperium and their quality of life score. Methods: A cross-sectional study on postpartum Spanish women was performed. Women older than 18 years and who had had a live birth were included. Less than 1% of women re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
(27 reference statements)
2
26
0
7
Order By: Relevance
“…Though adjusted by other variables, results from the regression analyses show that the difference between the above two groups is still large in terms of clinical relevance; maternal psychopathology after childbirth was profoundly associated with worse mental HRQoL. Our finding is consistent with previous studies [9,38]. Emmanuel et al found that even when they controlled for other confounding variables, having psychopathological symptoms was significantly associated with lower HRQoL in the period from late pregnancy to 12 weeks after childbirth [38].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Though adjusted by other variables, results from the regression analyses show that the difference between the above two groups is still large in terms of clinical relevance; maternal psychopathology after childbirth was profoundly associated with worse mental HRQoL. Our finding is consistent with previous studies [9,38]. Emmanuel et al found that even when they controlled for other confounding variables, having psychopathological symptoms was significantly associated with lower HRQoL in the period from late pregnancy to 12 weeks after childbirth [38].…”
Section: Discussionsupporting
confidence: 91%
“…Emmanuel et al found that even when they controlled for other confounding variables, having psychopathological symptoms was significantly associated with lower HRQoL in the period from late pregnancy to 12 weeks after childbirth [38]. Martínez-Galiano et al found that a significant decrease in HRQoL occur in women with depressive symptoms and anxiety [9]. In the early postpartum period, psychopathological symptoms have been shown to affect women’s ability to function, mental health status, inter-personal relationships, social engagement, and overall quality of life [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This period is characterized by physiological, physical, social and emotional changes for the mothers and their families that require the members therein to take on new roles and responsibilities (Ahmadi et al, 2014). Most problems occur in the first days of this period and last for six weeks and up to one year after delivery (Martínez-Galiano et al, 2019). The symptoms include fatigue, sleep disorders, nausea, anxiety, depression, sexual problems, physical function and dissatisfaction with partner support (Bahrami, Karimian, & Bahrami, 2014;Insana, Costello, & Montgomery-Downs, 2011;Medina, Lederhos, & Lillis, 2009;Parker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%